Video capture and post-processing technique for approximating 3D projectile trajectory - Pfeifer, C. M.; Burnfield, J. M.; Cesar, G. M.; Twedt, M. H.; Hawks, J. A. (Sports Technology, 2015)
In this paper we introduce a low-cost procedure and methodology for markerless projectile tracking in three-dimensional (3D) space. Understanding the 3D trajectory of an object in flight can often be essential in examining variables relating to launch and landing conditions. Many systems exist to track the 3D motion of projectiles but are often constrained by space or the type of object the system can recognize (Qualisys, Göteborg, Sweden; Vicon, Oxford, United Kingdom; OptiTrack, Corvallis, Oregon USA; Motion Analysis, Santa Rosa, California USA; Flight Scope, Orlando, Florida USA). These technologies can also be quite expensive, often costing hundreds of thousand dollars. The system presented in this paper utilizes two high-definition video cameras oriented perpendicular to each other to record the flight of an object. A post-processing technique and subsequent geometrically based algorithm was created to determine 3D position of the object using the two videos. This procedure and methodology was validated using a gold standard motion tracking system resulting in a 4.5 ± 1.8% deviation from the gold standard.